Eco-ELT for environmental research and praxis in ELT - Saiful, Jepri Ali (Universitas Islam Negeri Palangka Raya, Indonesia, 2023)
Global environmental catastrophes affecting present planetary ecosystems necessitate immediate and coordinated actions from all sectors and disciplines, including English language teaching (ELT). ELT shares the responsibilities with other disciplines to address ecological crises like climate change and biodiversity loss. However, environmental research and praxis in ELT lack of movement due to lack of unifying concept. An existing related concept, Eco-ELT, focuses solely on ecocriticism approach in ELT, limiting its scope. In fact, environmental research and praxis in ELT can take many forms, approaches, and models. For that reason, this conceptual article extends the Eco-ELT by elaborating on its philosophical standpoints: ontology, epistemology, and axiology. It also presents the Eco-ELT principle and framework of practice for English teachers, curriculum designers, and policymakers to implement the Eco-ELT intervention in English education. Finally, it elucidates the Eco-ELT research principle and area. These complete elaborations of the Eco-ELT aim to enhance and organize the structure of environmental movement in ELT and advance the contributions of ELT in decolonizing the Earth.